2009
DOI: 10.1371/journal.pone.0006409
|View full text |Cite
|
Sign up to set email alerts
|

CB2 Cannabinoid Receptors Contribute to Bacterial Invasion and Mortality in Polymicrobial Sepsis

Abstract: BackgroundSepsis is a major healthcare problem and current estimates suggest that the incidence of sepsis is approximately 750,000 annually. Sepsis is caused by an inability of the immune system to eliminate invading pathogens. It was recently proposed that endogenous mediators produced during sepsis can contribute to the immune dysfunction that is observed in sepsis. Endocannabinoids that are produced excessively in sepsis are potential factors leading to immune dysfunction, because they suppress immune cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 52 publications
(42 reference statements)
2
56
0
Order By: Relevance
“…It has been shown that Cnr2 signaling and the Alox5 pathway are both involved in the regulation of leukocyte migration (22)(23)(24). Previous studies showed that cannabidiol inhibits tumor cell growth by down-regulating the activity and expression of Alox5 (38), and it was also shown that there is a cooperative antineurotoxic effect between a selective Cnr2 agonist (JWH-015) and a specific Alox5 inhibitor (REV 5901) in THP-1 cells in vitro (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that Cnr2 signaling and the Alox5 pathway are both involved in the regulation of leukocyte migration (22)(23)(24). Previous studies showed that cannabidiol inhibits tumor cell growth by down-regulating the activity and expression of Alox5 (38), and it was also shown that there is a cooperative antineurotoxic effect between a selective Cnr2 agonist (JWH-015) and a specific Alox5 inhibitor (REV 5901) in THP-1 cells in vitro (56).…”
Section: Discussionmentioning
confidence: 99%
“…Cnr1 is highly expressed in the central nervous system and less in peripheral tissues (19), while Cnr2 is predominantly expressed in cells of hematopoietic origin in both mice and humans (20,21). Previous studies of the human and mouse cannabinoid system have shown that Cnr2 modulates the inflammatory migration of immune cells through many pathways and participates in the progression of many important autoimmune diseases (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). To confirm our chemical genetic screening, we generated mutant alleles of zebrafish cnr2 (gene encoding Cnr2) and found that leukocyte migration is enhanced by the inactivation of Cnr2, further confirming that Cnr2 acts as a conserved negative inflammatory regulator in the vertebrate.…”
mentioning
confidence: 99%
“…Moreover, inconsistencies are found regarding the expression of the CB receptors [27,36,56,57,[69][70][71][72][73][74][75][76][77]. Importantly, studies that reported a lack of CB 2 were performed using cell preparations in which contaminating eosinophils were removed [27,36].…”
Section: Discussionmentioning
confidence: 99%
“…(35) However, research on the modulation of these receptors has also provided some contradictory results. (36,37) A study by Tschöp et al modulated the CB 2 receptor in a systemic septic model induced through cecal ligation and puncture (CLP) in mice. (36) They observed reduced survival time of CB 2 receptor knockout mice compared to wild type mice during systemic sepsis.…”
Section: Endocannabinoid Receptorsmentioning
confidence: 99%
“…All of these results indicated that CB 2 receptor activation during systemic sepsis increased IL-10 overproduction causing an increase in bacterial invasion into the blood, ultimately resulting in increased mortality rates. (37) Multiple factors may help explain the inconsistency reported in studies of manipulating the CB 2 receptor during a septic state. (36,37) A possible explanation could be the severity of sepsis, where certain factors may play a crucial role in determining the role of the endocannabinoid receptors.…”
Section: Endocannabinoid Receptorsmentioning
confidence: 99%